2007
DOI: 10.1007/978-3-540-72588-6_154
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Approach for Analysis of Factors Affecting Crude Oil Price

Abstract: Abstract. In this paper, a new hybrid approach is presented to analyze factors affecting crude oil price using rough set and wavelet neural network. Related factors that affect crude oil price are found using text mining technique and Brent oil price is chosen as the decision price because it plays an important role in world crude oil markets. The relevant subsets of the factors are discovered by rough set module and the main factors are got, and then the important degrees of these are measured using wavelet n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Xu et al [44] employed text mining techniques to evaluate the related factors affecting oil prices and found that the world's total demand and supply are the most crucial factors, while demand is dominant. Furthermore, they also found that world economic growth and exchange rates affect crude oil prices as well and increase their volatility.…”
Section: Sentiment Analysis Application and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [44] employed text mining techniques to evaluate the related factors affecting oil prices and found that the world's total demand and supply are the most crucial factors, while demand is dominant. Furthermore, they also found that world economic growth and exchange rates affect crude oil prices as well and increase their volatility.…”
Section: Sentiment Analysis Application and Resultsmentioning
confidence: 99%
“…Xu et al [44] utilized text mining techniques that involved TF-IDF metrics and a K-mixture model to select attributes from a document collection. Therefore, in order to reduce the number of attributes selected, the authors applied the rough sets theory, whose main assumption is that every object in the universe of discourse is associated with some information.…”
Section: Sentiment Analysis Techniquesmentioning
confidence: 99%
“…Xu et al [94] proposed a rough set and wavelet neural networks (RSWNN) hybrid model for analyzing the factors that affected crude oil prices and predict future prices. Their approach consisted of text mining, rough set and wavelet neural networks.…”
Section: Applications Of Hybridized and Single CI Techniques In Crudementioning
confidence: 99%